Inhibition of p38-MAPK Signaling Pathway Attenuates Breast Cancer Induced Bone Pain and Disease Progression in a Murine Model of Cancer-Induced Bone Pain. Issue 1 (20th October 2011) - Sukhtankar, Devki; Okun, Alec; Chandramouli, Anupama; Nelson, Mark A; Vanderah, Todd W; Cress, Anne E; Porreca, Frank; King, Tamara
Background: Mechanisms driving cancer-induced bone pain are poorly understood. A central factor implicated to be a key player in the process of tumorigenesis, osteoclastogenesis and nociception is p38 MAPK. We determined the role of p38 MAPK in a mouse model of breast cancer induced bone pain in which mixed osteolytic and osteoblastic remodeling occurs. Results: In cancer-treated mice, acute as well as chronic inhibition of p38 MAPK with SB203580 blocked flinching and guarding behaviors in a dose-dependent manner whereas no effect on thresholds to tactile stimuli was observed. Radiographic analyses of bones demonstrated that chronic inhibition of p38 MAPK reduced bone loss and incidence of spontaneous fracture in cancer-treated mice. Histological analysis of bones collected from mice treated with the p38 MAPK inhibitor showed complete absence of osteoblastic growth in the intramedullary space as well as significantly reduced tumor burden. Conclusions: Blockade of non-evoked pain behaviors but not hypersensitivity suggests differences in the underlying mechanisms of specific components of the pain syndrome and a possibility to individualize aspects of pain management. While it is not known whether the role of p38 MAPK signaling can be expanded to other cancers, the data suggest a need for understanding molecular mechanisms and cellular events that initiate and maintain cancer-induced bone pain for effective management for both ongoing pain as well as breakthrough pain.